Direct Effects of Light on Sleep under Ultradian Light-Dark Cycles Depend on Circadian Time and Pulses Duration - Fanny Fuchs; Ludivine Robin-Choteau; Laurence Hugueny; Dominique Ciocca; Patrice Bourgin (Clocks & Sleep, 2022)
Ultradian light–dark cycles in rodents are a precious tool to study the direct effects of repeated light exposures on sleep, in order to better understand the underlying mechanisms. This study aims to precisely evaluate the effects of light and dark exposures, according to circadian time, on sleep and waking distribution and quality, and to determine if these effects depend on the duration of light and dark pulses. To do this, mice were exposed to 24 h-long ultradian light–dark cycles with different durations of pulses: T2 cycle (1 h of light/1 h of dark) and T7 cycle (3.5 h of light/3.5 h of dark). Exposure to light not only promotes NREM and REM sleep and inhibits wake, but also drastically alters alertness and modifies sleep depth. These effects are modulated by circadian time, appearing especially during early subjective night, and their kinetics is highly dependent on the duration of pulses, suggesting that in the case of pulses of longer duration, the homeostatic process could overtake light direct influence for shaping sleep and waking distribution.